Examining evidence for a relationship between human-animal interactions and common mental disorders during the COVID-19 pandemic: a systematic literature review - Barr, H. K.; Guggenbickler, A. M.; Hoch, J. S.; Dewa, C. S. (Frontiers in Health Services, 2024)
Introduction COVID-19 lockdowns, shelter in place, closures of transportation and mental health services, and dearth of mental health providers created new barriers to obtaining support for mental health needs at a time of increased rates of anxiety and depression. During the pandemic, a record number of households owned and adopted pets, opening a potential avenue to investigate the relationship between pets and mental health. This systematic literature review examined the question: What is the evidence for a relationship between human-animal interaction and/or animal ownership and common mental disorders among adults who interacted with pets compared to adults who did not during the COVID-19 pandemic? Methods To address this question, four databases were searched: Medline, PsycINFO, Web of Science, and SCOPUS for peer-reviewed literature published between 2020 and July 2023. Of the 1,746 articles identified by the searches, 21 studies were included in this review. Results Results suggest that there exists a relationship between animal ownership and strong pet attachment and pet interaction, though the directionality of the relationship was not investigated by the included studies. There was an association between having a stronger relationship with a pet and lower feelings of depression and other mental health symptoms. There was also evidence of an association between anxiety and higher levels of animal attachment. Conclusion Understanding the association between human-animal interaction and common mental disorders may be helpful to clinicians assessing the mental health of clients. Clinicians may glean additional insight about stressors, risk factors, social supports, and lifestyle of clients based on the client's status as a pet owner. Future research could further explore the direction of the causal relationship of human-animal interaction and/or animal ownership on common mental disorders; this could further inform how the HAI relationship can be used to support clients with mental health struggles.